SOME FEATURES OF THE ANTARCTIC SEA ICE OBSERVED FROM MESSR IMAGES - イシダ, クニミツ; オオシマ; ヤマノウチ, タカシ; カンザワ, ヒロシ; ISHIDA, Kunimitsu; OHSHIMA, Kay I.; YAMANOUCHI, Takashi; KANZAWA, Hiroshi (National Institute of Polar Research, 1997)
P(論文) We describe some features of Antarctic sea ice using the Multispectral Electronic Self Scanning Radiometer (MESSR) installed on MOS-1/1b satellites. MESSR images have the advantage of high spatial resolution, approximately 50m. This makes possible, for the first time, the observation of the ice band features and of their variations. Ice bands can often be seen from the ice edge to the ice interior zone throughout the year and they extend hundreds of kilometers in the latitudinal direction. We found that the width and spacing of ice bands tend to decrease from winter to spring. The band width is 2-10km in August, whereas it is only 0.2-3km in December. Ice streamers, which are composed frazil ice and new ice, are observed in the coastal polynya off land-fast ice and Breid Bay. departmental bulletin paper